Effect of temperature on the fracture energy of adhesive layers of engineered wood - Zhang, Zhongwen (2022)
Adhesive layers in engineered wood are critical for shear stress transfer, particularly under load-bearing conditions. Though there is some data on the shear strength of the adhesive layers, there is limited data on their fracture energy and how it varies with temperature. Understanding the fracture energy could reduce the inconsistencies caused by stress singularity and crack nucleation in a shear strength testing methodology. Therefore, in this article, a 4-pointing bending test framework was used to investigate the fracture energy of the adhesive layers at different temperatures. It is found that the fracture energy of the adhesive layer bonding the 0o/90o (cross-laminated) oriented timber plies is ∼30% lesser than that of the layer bonding 0o/0o (parallel) plies. More importantly, irrespective of the arrangement/orientation of the plies, a steady decline in fracture energy is seen with increase in temperature. For instance, by ∼130oC, the fracture energy of the adhesive layer has reduced by ∼53% in a cross-laminated state and ∼39% for those plies bonded in 0o/0o orientation. Finite element analysis was also conducted based on the cohesive elements and cohesive zone model for validation of the experimentally measured fracture energy.